Chronic experimental autoimmune encephalomyelitis is an excellent model to study neuroaxonal degeneration in multiple sclerosis - Voskuhl, Rhonda R.; MacKenzie-Graham, Allan (Frontiers in Molecular Neuroscience, 2022)
Animal models of multiple sclerosis (MS), specifically experimental autoimmune encephalomyelitis (EAE), have been used extensively to develop anti-inflammatory treatments. However, the similarity between MS and one particular EAE model does not end at inflammation. MS and chronic EAE induced in C57BL/6 mice using myelin oligodendrocyte glycoprotein (MOG) peptide 35–55 share many neuropathologies. Beyond both having white matter lesions in spinal cord, both also have widespread neuropathology in the cerebral cortex, hippocampus, thalamus, striatum, cerebellum, and retina/optic nerve. In this review, we compare neuropathologies in each of these structures in MS with chronic EAE in C57BL/6 mice, and find evidence that this EAE model is well suited to study neuroaxonal degeneration in MS.